Daily physical activity and trajectories of care service use among older adults: the HUNT4 Trondheim 70+ study - Astrid Ustad; Trine Holt Edwin; Kjerstin Næss Melsæter; Karen Sverdrup; Karen Sverdrup; Gro Gujord Tangen; Gro Gujord Tangen; Øystein Døhl; Øystein Døhl; Pernille Thingstad; Pernille Thingstad; Beatrix Vereijken; et al. (Frontiers in Public Health)
IntroductionUnderstanding factors that influence care service use is crucial for developing preventive strategies to maintain independence among older adults. In this study, we aimed to identify distinct trajectory groups of municipal care service use among community-dwelling older adults to determine whether daily physical activity is associated with future care service use.MethodsThis prospective cohort study included 981 community-dwelling older adults from the HUNT4 Trondheim 70+ study. At baseline, physical activity was assessed over seven consecutive days using two accelerometers attached to the thigh and lower back. An activity type machine learning model was used to classify the physical activity types: walking, standing, cycling, running, sitting, and lying. Municipal care service use was retrieved monthly from medical records for 3 years. Using group-based trajectory modeling, we identified distinct trajectories of care service use. Multinomial regression models adjusted for age, sex, education level, dementia, and physical performance were used to evaluate the associations between daily physical activity at baseline and care service group belonging.ResultsWe identified four distinct trajectory groups of municipal care service use, labeled steady low (72.7%), low increasing (9.0%), medium increasing (12.0%), and high increasing (6.3%). Daily time spent in total physical activity was not associated with trajectory group belonging when adjusted for age, sex, education level, dementia, and physical performance. However, more time spent walking, in bouts lasting longer than a minute, was associated with a reduced relative risk of belonging to the high increasing compared to the steady low group. Furthermore, age, physical performance, and dementia were all significantly associated with trajectory group belonging, and sex differences were observed. Compared to women, men had a reduced relative risk of belonging to the low increasing, medium increasing, or high increasing trajectory groups.ConclusionThis study identified four distinct trajectories of municipal care service use among older adults over 3 years. Total daily physical activity was not associated with trajectories of care service use, but more time spent walking in longer bouts was independently associated with lower care service use, even when adjusted for the strong predictors of physical performance, dementia diagnosis, and age.